2020
DOI: 10.7717/peerj.8662
|View full text |Cite
|
Sign up to set email alerts
|

Engrailed-2 promotes a malignant phenotype of esophageal squamous cell carcinoma through upregulating the expression of pro-oncogenic genes

Abstract: Background A number of homeobox genes have been implicated in the development of various cancers. However, the role of engrailed 2 (EN2), a member of the homeobox gene superfamily, in esophageal squamous cell carcinoma (ESCC) remains unknown. Methods The expression of EN2 was examined using quantitative real-time PCR and immunohistochemistry. A stable cell line was established to express exogenous EN2 using a lentivirus system. The malignant phenotype was analyzed with proliferation, clonogenicity, wound-hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…In addition, disorders of EN2 regulation can lead to abnormal cell proliferation, leading to tumorigenesis. Studies show that EN2 plays an important role in the proliferation, migration, and invasion of various tumor cells, including prostate cancer, colorectal cancer, esophageal squamous cell carcinoma, lung cancer, and bladder cancer, and is closely related to the poor prognosis of tumor patients ( Zhou et al, 2017 ; Lin et al, 2018 ; Cao et al, 2020 ; Li et al, 2020 ; Li et al, 2021 ). EN2 promotes the proliferation and invasion of colorectal cancer cells by regulating CCL20, thus promoting the progression of colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, disorders of EN2 regulation can lead to abnormal cell proliferation, leading to tumorigenesis. Studies show that EN2 plays an important role in the proliferation, migration, and invasion of various tumor cells, including prostate cancer, colorectal cancer, esophageal squamous cell carcinoma, lung cancer, and bladder cancer, and is closely related to the poor prognosis of tumor patients ( Zhou et al, 2017 ; Lin et al, 2018 ; Cao et al, 2020 ; Li et al, 2020 ; Li et al, 2021 ). EN2 promotes the proliferation and invasion of colorectal cancer cells by regulating CCL20, thus promoting the progression of colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…EN2 also promotes the invasion and metastasis of esophageal squamous cell carcinoma by upregulating SPARC expression. It promotes the proliferation, invasion, and metastasis of bladder cancer cells by activating the PI3K/Akt pathway and inhibiting the PTEN gene ( Cao et al, 2020 ; Li et al, 2020 ) ( Li et al, 2021 ). In addition, it was found that EN2 expression levels are also correlated with the degree of malignancy of gliomas and promoted the malignant progression of glioma ( Zeng et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The pleiotropy of En (McGrath et al, 2013;Wizenmann et al, 2015;Punia et al, 2019;Cao et al, 2020) gives rise to a wide variety of mutation phenotypes of en, such as scutellar cleft, malformation of the wing, an extra sex comb and lethality in D. melanogaster (Lindsley and Zimm, 1992). Two spermathecae arise from the anterior compartment of female genital primordia of the A8 segment in the wild type female genital disc during the pupal stage.…”
Section: Discussionmentioning
confidence: 99%
“…En is well known as a homeodomaincontaining transcription factor that plays important roles in boundary formation (Kornberg, 1981;Kornberg et al, 1985). En family proteins were recently revealed to be considerably pleiotropic, having three primary functions in many metazoans: transcription regulation, translation control and action in extracellular signaling pathways (reviewed by McGrath et al, 2013;Wizenmann et al, 2015;Punia et al, 2019;Cao et al, 2020). However, the molecular basis of numerical variation in spermathecae is yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported 27 that EN2 has an oncogenic role in esophageal squamous cell carcinoma. In the present work, we showed that the expression of EN2 was increased in tissue samples derived from patients with non-small cell lung cancer (NSCLC).…”
mentioning
confidence: 99%